Frequency of type 2 diabetes mellitus in patients with chronic hepatitis C virus infection presenting to a tertiary care hospital - Ahmad, Bilal; Ahmad, Miraj; Idrees, Muhammad; Rahman, Gohar; Ahmad, Waqar; Ahmad, Jawad (International Journal of Pathology, 2025)
Background: Chronic Hepatitis C Virus (HCV) infection poses significant public health challenges, not only due to its hepatic-related complications but also its association with metabolic disorders including Type 2 Diabetes Mellitus (T2DM). Understanding the frequency and contributing factors of T2DM in HCV patients is crucial for improving diagnosis, treatment, and outcomesMethods: This prospective study was conducted at the Medical Unit of Lady Reading Hospital, Peshawar Pakistan, from April to September 2021. A total of 200 HCV-seropositive patients aged 18–75 years were included. The diagnosis of HCV was confirmed through ELISA, and T2DM was determined based on HbA1c levels. Data on demographics, clinical parameters, and laboratory findings were collected. Statistical analysis was done which included univariate and multivariate logistic regression, to identify significant predictors of T2DM.Results: The prevalence of T2DM among HCV-seropositive patients was 37%. Key risk factors for T2DM included cirrhosis (OR = 2.005, 95% CI: 1.15–3.43), age ≥40 years, obesity, male gender, and a family history of diabetes (P < 0.05). Patients with cirrhosis had a significantly higher prevalence of T2DM, especially those aged >60 years. Overall, 61% of participants were overweight, 19% were obese, and 20% had normal BMI. Multivariate analysis highlighted cirrhosis and metabolic factors as significant contributors to T2DM risk.Conclusion: T2DM is highly prevalent among chronic HCV patients, particularly those with older age, having liver cirrhosis, obesity, and a family history of diabetes. Early screening and integrated management of metabolic and liver-related complications are essential for improving patient outcomes.